Targeting the noradrenergic system for anti-inflammatory and neuroprotective effects: implications for Parkinson's disease. - Harkin, Andrew; O'Neill, Eoin (My University, 2018)
Degeneration of the locus coeruleus noradrenergic system is thought to play a key role in the pathogenesis of Parkinson’s disease (PD), whereas pharmacological approaches to increase noradrenaline bioavailability may provide neuroprotection. Noradrenaline inhibits microglial activation and suppresses pro-inflamma - tory mediator production ( e.g ., tumor necrosis factor-α, interleukin-1β & inducible nitric oxide synthase activity), thus limiting the cytotoxicity of midbrain dopaminergic neurons in response to an inflamma - tory stimulus. Neighbouring astrocyte populations promote a neurotrophic environment in response to β 2 -adrenoceptor (β 2 -AR) stimulation via the production of growth factors ( e.g ., brain derived neurotrophic factor, cerebral dopamine neurotrophic factor & glial cell derived neurotrophic factor which have shown promising neuroprotective and neuro-restorative effects in the nigrostriatal dopaminergic system. More recent findings have demonstrated a role for the β 2 -AR in down-regulating expression levels of the human α-synuclein gene SNCA and relative α-synuclein protein abundance. Given that α-synuclein is a major protein constituent of Lewy body pathology, a hallmark neuropathological feature in Parkinson’s disease, these findings could open up new avenues for pharmacological intervention strategies aimed at alleviating the burden of α-synucleinopathies in the Parkinsonian brain. In essence, the literature reviewed herein supports our hypothesis of a tripartite neuroprotective role for noradrenaline in combating PD-related neuropathology and motor dysfunction via (1) inhibiting nigral microglial activation & pro-inflammatory mediator production, (2) promoting the synthesis of neurotrophic factors from midbrain astrocytes and (3) downregulating α-synuclein gene expression and protein abundance in a β 2 -AR-dependent manner. Thus, taken together, either pharmacologically enhancing extra-synaptic noradrenaline bioavailability or targeting glial β 2 -ARs directly makes itself as a promising treatment option aimed at slowing/halting PD progression
PUBLISHED
Keywords: Locus coeruleus noradrenergic system; Noradrenaline; Microglia; Astrocytes; Inflammation; Parkinson's disease; Neuroprotection; Animal model; Dopamine; locus coeruleus noradrenergic system; Immunology, Inflammation & Infection; Neuroscience; Age-related disability; Chronic Health Condition; Mental Health/Psychosocial disability; Health